NEW SPECIES OF RADIOLARIA FROM THE ISLAND OF BUTON, SOUTH EAST SULAWESI - Soemoenar Soeka (Scientific Contributions Oil and Gas, 2019)
Soeka (1991) reported 30 new species of radiolarians, 3 new genera, and several undetermined species from the Tobelo Formation, Buton Island, South East Sulawesi. Among the undetermined spesies are proposed as new spesies and presented in this report. Those new species are: 1. Actinomma panujui Soeka; sp. nov.; 2. Orbiculiforma eocenica Soeka; 3. Spongotrochus kholiqi Soeka, sp. nov.; 4. Spongotrochus buskamali Soeka, sp. nov.; 5. Spongotrochus iskandari Soeka, sp. nov.; 6. Sethodiscus (Sethodiscinus) imami Soeka, sp. nov.; 7. Lichnocanoma rasantyoi Soeka, sp. nov.; and 8. Sethocapsa transitoria Soeka.